2009
DOI: 10.1111/j.1939-165x.2009.00160.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential cell counts in canine cytocentrifuged bronchoalveolar lavage fluid: a study on reliable enumeration of each cell type

Abstract: A 500-cell differential count is required for all types of cells to be quantified with adequate reproducibility in canine cytocentrifuged BAL fluid samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 14 publications
2
19
0
Order By: Relevance
“…None of the dogs had BAL fluid submitted for viral screening or assessment of novel pathogens that might have contributed to lymphocytosis. Our clinical pathology laboratory routinely performs differential cytology on a count of 200 cells; however, 1 study indicated that this methodology does not provide reproducible results between observers for lymphocyte identification . Finally, we elected to include all cases that had at least 1 BAL site with >20% lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…None of the dogs had BAL fluid submitted for viral screening or assessment of novel pathogens that might have contributed to lymphocytosis. Our clinical pathology laboratory routinely performs differential cytology on a count of 200 cells; however, 1 study indicated that this methodology does not provide reproducible results between observers for lymphocyte identification . Finally, we elected to include all cases that had at least 1 BAL site with >20% lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In the veterinary literature, no reports describing methods for producing reliable mast cell counts in BAL fluid were found. A recent study determined that a 500‐cell differential ensured adequate reproducibility of cell counts in canine BAL fluid samples, however, mast cells were not included in the differential (presumably due to species differences in cytologic patterns of respiratory disease) . For eosinophils, the same study determined that counting 200 cells was enough to produce adequate reliability, speculating that eosinophils are easily recognized despite being present in relatively low numbers.…”
Section: Discussionmentioning
confidence: 99%
“…The ICC is reported between 0.0 and 1.0, where the closer to 1.0 the less error is present between raters. As indicated by another study a threshold of > 0.90 reflects high reproducibility and a threshold of > 0.85 reflects adequate reproducibility . For the category of LAI (normal, mild to moderate, or severe), inter‐rater reliability for each method was determined using Cronbach's α, the mean ICC across 3 raters.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The accuracy of these counts may be questionable due to increased mucus and lack of standardization of techniques; however, cell counts are crucial following a BAL to establish adequacy of the sample (Hawkins and DeNicola, 1989). Thus, a standard procedure that includes a 500-cell differential has been recommended (De Lorenzi et al, 2009). Recent studies have suggested the use of urea dilution to standardize the cellular and noncellular components of BAL fluid samples for more adequate analysis of nucleated cell counts in epithelial lining fluid (Mills and Litster, 2006).…”
Section: Bronchoalveolar Lavagementioning
confidence: 99%